New Peripheral Centralities - Apostolos Kyriazis (European Regional Science Association (ERSA), 2006)
The expansion of the European Union, the re-negotiation of the cohesion funds, the shrinkage of the public investments programme and the existing laws lead the middle-sized Greek cities to be in a disadvantageous position within the European urban network, while major urban problems still exist. The meaning of the words "Periphery" and "Centralities" changes its scale always preserving their inbetween ratio, depending on its use (i.e. continental - national – urban) the same way that Architecture does (from urban planning to industrial and detail design). The exploitation of the lost urban space (and time) based on existing urban planning legislation is a common target. The "Active city blocks" regeneration tool is able to provide the cities with new centralities, new landmarks and some new mobility. This paper is about some draft thoughts concerning the implementation of urban planning projects (about the rejuvination of existing urban areas of great density), combined with recent discussions on factors that give shape to Greece's urban environment (for example withdrawal of semi-open spaces, basements added at total sq.m measurements, backyards etc.) to be regulated. The urban regeneration and the upgrade of the cities' environmental standards remain a main objective. In addition to the aforementioned, some indirect objectives can also be achieved, such as the stimulation of the constructions sector, the diminishing of social segregation and the enrichment of the existing architectural typology.
Keywords: 330